Measurement of inclusive charged-current νμ scattering on hydrocarbon at ⟨Eν⟩ ∼6 GeV with low three-momentum transfer - Ascencio-Sosa, M.V.; Andrade, D.A.; Mahbub, I.; Akhter, S.; Ahmad Dar, Z.; Akbar, F.; Ansari, V.; Bashyal, A.; Bender, S.; Bercellie, A.; Betancourt, M.; Bodek, A.; et al. (American Physical Society, 2022)
The MINERνA experiment reports double-differential cross-section measurements for 𝜈µ-carbon interactions with three-momentum transfer |q⃗ | < 1.2 GeV obtained with medium energy exposures in the NuMI beam. These measurements are performed as a function of the three-momentum transfer and an energy transfer estimator called the available energy defined as the energy that would be visible in the detector. The double-differential cross sections are compared to the GENIE and NuWro predictions along with the modified version of GENIE which incorporates new models for better agreement with earlier measurements from MINERνA. In these measurements, the quasielastic, resonance, and multinucleon knockout processes appear at different kinematics in this two-dimensional space. The results can be used to improve models for neutrino interactions needed by neutrino oscillation experiments.
Keywords: Physics; Neutrino; Nuclear physics; Algorithm; Computer science; https://purl.org/pe-repo/ocde/ford#1.03.03